1990
DOI: 10.1084/jem.172.5.1509
|View full text |Cite
|
Sign up to set email alerts
|

Widespread intradermal accumulation of mononuclear leukocytes in lepromatous leprosy patients treated systemically with recombinant interferon gamma.

Abstract: Intradermal administration of recombinant interferon gamma (rIFN-gamma) to lepromatous leprosy patients has converted the local histology toward a tuberculoid pattern. However, such changes have been confined to the site of injection. In contrast, in the present study, marked, intradermal accumulation of CD3+, CD4+, CD8+, and CD1a+ T cells and Leu-M5+ mononuclear phagocytes was induced at a distance from the sites of administration, in a dose-dependent manner, by 10 daily intramuscular injections of 10-30 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…It is possible that activated peripheral monocytes increased the clearance of dead bacteria within the lesion. In more recent studies, administration of recombinant IFN-,y in sites distant from the lepromatous lesion appear to confirm the beneficial effect of the cytokine [28]. Marked intralesional accumulation of CD3 +, CD4 +, CD8 + and CDa + T cells was observed with a dose of 10 to 30#g of recombinant IFNT/m 2 [28], converting the lepromatous lesion into a tuberculoid lesion.…”
Section: Leprosymentioning
confidence: 79%
“…It is possible that activated peripheral monocytes increased the clearance of dead bacteria within the lesion. In more recent studies, administration of recombinant IFN-,y in sites distant from the lepromatous lesion appear to confirm the beneficial effect of the cytokine [28]. Marked intralesional accumulation of CD3 +, CD4 +, CD8 + and CDa + T cells was observed with a dose of 10 to 30#g of recombinant IFNT/m 2 [28], converting the lepromatous lesion into a tuberculoid lesion.…”
Section: Leprosymentioning
confidence: 79%
“…Enhancement of CMI and upgrading of clinical and histopathological classification has been attempted in borderline lepromatous and LL patients via cytokine immunotherapy. Upon injection of IFN-␥ or IL-2 into leprosy lesions, a marked cellular infiltration occurred (23,24,40), and the bacillary index, a measure of M. leprae burden, was reported to markedly decrease (41). Thus, treatment of lesions with Th1 cytokines apparently evoked a CMI response, but the effect was transient; the specific unresponsiveness to M. leprae Ags characteristic of multibacillary disease was not reversed.…”
Section: Discussionmentioning
confidence: 94%
“…First, numerous tumor models have shown that M can act as killer cells and attack abnormal cells (17)(18)(19)(20)(21)(22). Second, immunotherapy with Th1-type cytokines in LL patients demonstrated upgrading of clinical disease in the absence of specific T cell-mediated immunity (23,24).…”
mentioning
confidence: 99%
“…Bolus therapy with rIFN-ga (Polyferon, Bioferon, Laupfor the in vivo application of recombinant IFN-g (rIFN-g) therapy for patients with infectious diseases [4]. Systemic or heim, Germany) was administered following a previously described protocol [6]; the dose was 50 mg for the first day and local therapy with rIFN-g was found to be partially effective for leishmaniasis [5,6] and leprosy [7]. Furthermore, data from 100 mg for two consecutive days.…”
mentioning
confidence: 99%